2014
DOI: 10.1111/1440-1681.12220
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative ileus: mechanisms and future directions for research

Abstract: Postoperative ileus (POI) is an abnormal pattern of gastrointestinal motility characterized by nausea, vomiting, abdominal distension and/or delayed passage of flatus or stool, which may occur following surgery. Postoperative ileus slows recovery, increases the risk of developing postoperative complications and confers a significant financial load on healthcare institutions. The aim of the present review is to provide a succinct overview of the clinical features and pathophysiological mechanisms of POI, with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(172 citation statements)
references
References 154 publications
4
163
0
2
Order By: Relevance
“…[15,16] Postoperative pulmonary complication incidence of our study was 18.7%, which revealed that male gender, smoking history, coexistence of COPD, and psychiatric complication occurrence were the factors associated with higher risk for post-thoracotomy pulmonary complication incidence; all in accordance with the current literature.…”
Section: Discussionsupporting
confidence: 90%
“…[15,16] Postoperative pulmonary complication incidence of our study was 18.7%, which revealed that male gender, smoking history, coexistence of COPD, and psychiatric complication occurrence were the factors associated with higher risk for post-thoracotomy pulmonary complication incidence; all in accordance with the current literature.…”
Section: Discussionsupporting
confidence: 90%
“…Die Genese des PPI ist multifaktoriell, es wird die Beteiligung inflammatorischer und immunologischer Mediatoren [64], Störungen des autonomen und enterischen Nervensystems, Stö-rungen der Erregungsleitung im Bereich von Unterbrechungen der intestinalen Kontinuität, ödematöser Veränderungen der Darmwand durch Störungen der Flüs-sigkeitsbilanz, Elektrolytstörungen, Veränderungen gastrointestinaler Hormone und Neuropeptide sowie Nebenwirkungen der perioperativer Medikamentengabe angenommen (einen aktuellen Über-blick gibt [61]). …”
Section: Introductionunclassified
“…Factors include the complicated disturbances in immunological, inflammatory, neurological, and receptor-mediated functioning. [24] Pharmacological agents such as cyclooxygenase 2 (COX-2) inhibitors, ghrelin agonists, and opioid agonists always bring side effects, such as cardiovascular adverse events and immunosuppressive effects; laparoscopic technique has been proven to reduce the incidence of POI, while the costs minimize its use [10] . In addition to these treatments, acupuncture has become a promising option for gastrointestinal disease.…”
Section: Discussionmentioning
confidence: 99%